RELATIONSHIP BETWEEN MMP14 +7096 GENETIC VARIATION WITH CHILD TURCOTTE PUGH (CTP) SCORE IN HEPATIC CIRRHOSIS - Wijayana, Kamal Agung; Siswandari, Wahyu; Hapsari, Ariadne; Yudha, Paskalis Bhaskara Unggul (Medical and Health Journal, 2024)
Background: Hepatic cirrhosis is chronic hepatic damage followed by structural change and decreased function of hepar. Child Turcotte Pugh (CTP) score is used to assess the severity of hepatic cirrhosis. Genetic variation of MMP14 has a role in the progressivity of liver diseases. Relationship between MMP14 +7096 genetic variation and Child Turcotte Pugh score in hepatic cirrhosis was not well known.Aim: To determine the relationship between MMP14 +7096 genetic variation with Child Turcotte Pugh score in hepatic cirrhosis patients in Prof. Dr. Margono Soekarjo General Hospital Purwokerto.Methods: Analytical observational study with cross-sectional design was conducted among 30 patients who were diagnosed hepatic cirrhosis in Prof. Dr. Margono Soekarjo General Hospital Purwokerto. Data collection was performed by total samping of blood laboratory test and PCR-RFLP. Data was analysed using Kruskal-Wallis test and Mann-Whitney post hoc test.Results: Kruskal-Wallis test shows relationship between genetic variation of MMP14 +7096 with Child Turcotte Pugh (CTP) score (p=0,024). Mann-Whitney post hoc test shows significant relationship between CC and TT genotype (p=0,02).Conclusions: There is a significant relationship between CC and TT genotype MMP14 +7096 genetic variation with Child Turcotte Pugh score in hepatic cirrhosis patients in Prof. Dr. Margono Soekarjo General Hospital Purwokerto.